THE EFFECTIVENESS OF PEER COLLABORATION TECHNIQUE IN TEACHING SPEAKING AT SECOND GRADE STUDENTS OF MA DARUL HIKMAH DAREK - Khairul Wahyuni (Journal of English Education and Literature, 2025)
This research is intended to analyze the effectiveness the peer collaboration technique is helping second grade students at MA Darul Hikmah Darek to improve their speaking abilities. The method use in this study is quantitative approach with quasi-experimental design, which involved two groups: one received peer collaboration treatment, while the other taught using traditional teaching methods. The research instrument consisted of pre-tests and post-tests in the form of personal narrative speaking activities. Statistical analysis revealed a significant difference between the pre-test and post-test scores in both groups. However, the experimental group showed a greater improvement (60.21 to 93.32) compared to the control group (from 62.48 to 76.48). The result of the independent sample t-test indicated a significance value of 0.000 < 0.05, confirming that the peer collaboration technique had a significant positive effect on students’ speaking performance. These findings suggest that collaborative learning strategies can serve as an effective and interactive alternative in enhancing students’ communication skills in English language learning.